The public's reliance on satellite channels to get information about human rights issues - Alobaidi, Daham Ali Hussein (ALBAHITH ALALAMI, 2020)
The research aimed to study the role that the media play in shaping the public knowledge of human rights issues among the people of Kirkuk, which will be the focus of the study. The research was conducted by applying a survey panel to a random sample of the city's audience. The research dealt with the theoretical aspect of a theory that relied on the media, and the loans provided by the theory, on the basis of which the research was conducted and the research problem was determined based on a major question: What is the role that the mass media play in developing the knowledge of members of the public on human rights and the relationship between the intensity of view in that, as well as the identification of the effect of two variables Gender and education based on that and the research relied on the descriptive approach that uses the survey method by applying a questionnaire form to a random sample of town audience of 250 individuals, and the researcher used the median frequencies and annual ratios, and the application of square (2) to treat the statistical results and determine the relationship between the variables and the role of television in Water the public's knowledge of human rights.